Pemetaan Kajian Kepemimpinan Etis dalam Konteks Organisasi: Sebuah Scoping Literature Review (2018-2024) - Muhammad Hikam Faturrahman; Tria Raisya; Asep Irfan Asep Irfan Maulana3,; Pandu RA (INDO PUBLISHING, 2026)
Ethical leadership is an important concept in the study of leadership and organizational behavior because it plays a role in shaping organizational values, norms, and behavior. Although research on ethical leadership continues to evolve, the existing literature shows a diversity of focuses, methodological approaches, and organizational contexts being studied. This condition causes the understanding of the direction of ethical leadership studies to become fragmented. This research aims to map the main focus of the discussion, the research approach used, and the organizational context in the study of ethical leadership through the scoping literature review approach. Data were obtained from Google Scholar using the keywords